الدوطة فى بنغلاديش بين حكم الشرع والتقاليد الاجتماعية: دراسة تحليلية وتقويمية - نبي، محمد نور (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
Dowry is one of the imported customs in the Muslim community in the entire Indian sub-continent, and it is the major reason for the advent of domestic violence against women. The researcher was unable to find a study related to the issue from the juristic perspective. Investigating this issue is the most paramount task for emancipating the Muslim world from injustice and corruption. The researcher therefore, applied the method of induction and analytical by narrating the history of dowry in the ancient civilizations, its occurrence in the Muslim community, the Islamic judgment on it, its benefits, its evils and the solutions for its cancelation. The researcher also tried to elaborate some of the minor issues related to the study such as tradition, its Islamic point of reference, conditions for its consideration, its scopes, as well as the women's Islamic fiscal rights. Finally, the researcher arrived at the following results: the custom of dowry that has been widespread in the Indian sub-continent has no Islamic basis in the Qur'an and the Prophetic traditions as well as the Muslim consensus; this is the general opinion of the scholars and jurists. It is therefore, pertinent for the scholars and reformers to employ their utmost efforts in eradicating this heinous tradition through educating and guiding people to the right and fair path.